Buying at First Sight: Modelling the Determinants of UI on Generation Z’s E-Impulsive Buying Behaviour - Kaur, Arveen; Srivastava, Alpana; Trivedi, Shekhar; Srivastava, Priyanka; Dikshit, Shashi Kant (International Review of Management and Marketing, 2025)
Online shopping has become the dominant retail shopping choice in India, driven by Generation Z’s preference due to the seamless experience in e-commerce. This research examines how the user interface design elements - Social Influencers, Mannequin Display and Website Rewards influence Generation Z’s E-impulsive buying behaviour in Indian E-commerce markets. Random and Purposive sampling approach was adopted to collect 388 responses from Gen Z through a structured survey and questionnaire instrument floated via social media platforms. This research framework examined four constructs, namely Social Influencers, Mannequin Display, Website Rewards and E-Impulsive Buying and their relationship was tested using Structural Equation Modelling - SMARTPLS. Findings of this study revealed a significant positive relationship between social influencers and e-impulsive buying (β = 0.211, P = 0.009), rewards and e-impulsive buying (β = 0.658, P = 0.000) and mannequin display with e-impulsive buying (β = 0.197, P = 0.028). This study provides theoretical and practical implications based on the real-world scenario for interface designers and e-businesses to increase their market reach and shoppers’ engagement in India’s digital marketplace.